Cross-border hybrid instruments - Niels Johannesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2012)
The rules demarcating debt and equity for tax purposes differ across countries, hence the possibility that a hybrid instrument is treated as equity in one country and debt in another and that a ?rm with foreign investment can combine tax favored dividend income in the home country and tax deductible interest expenses in the foreign country. This paper characterizes the scope for cross-border hybrid instruments as a function of the properties of demarcation rules. For any given pair of countries, ?rms in at least one country and sometimes in both can ?nance investment in the other country with a cross-border hybrid instrument. When hybrid instruments can be embedded in multi-layered ?nance structures, fi?rms in both countries can always achieve equity treatment in the home country and debt treatment in the host country.
Keywords: 330; Steuerplanung; Steuerrecht; Internationale Unternehmensfinanzierung; Theorie